Marcos, Brocka, Bernal, City Films, and the Contestation for Imagery of Nation - Tolentino, Rolando B. (Archīum Ateneo, 2024)
The essay maps out the contestation for imagery of nation with the Marcoses on the one hand, and two of the most outstanding filmmakers of the era on the other hand. The Marcoses set out a megalomania of infrastructures and images that echoed the Imeldific vision of “the true, the good, and the beautiful.” I counterpose the major city films of Lino Brocka (Maynila: Sa mga Kuko ng Liwanag) and Ishmael Bernal (Manila by Night) to provide a contest to the official imagery of the nation. These two films uniquely evoke an intimate dialog with and critique of the Marcoses’ design of (what eventually became) Metro Manila and the nation, figuring contrary bodies and responses as consequences of collective lives under the jurisdiction and administration of the conjugal dictatorship.